2015
DOI: 10.3233/jpd-140355
|View full text |Cite
|
Sign up to set email alerts
|

Load-Dependent Interference of Deep Brain Stimulation of the Subthalamic Nucleus with Switching from Automatic to Controlled Processing During Random Number Generation in Parkinson’s Disease

Abstract: Background: Deep brain stimulation of the subthalamic nucleus (STN DBS) ameliorates the motor symptoms of Parkinson’s disease (PD). However, some aspects of executive control are impaired with STN DBS.Objective: We tested the prediction that (i) STN DBS interferes with switching from automatic to controlled processing during fast-paced random number generation (RNG) (ii) STN DBS-induced cognitive control changes are load-dependent.Methods: Fifteen PD patients with bilateral STN DBS performed paced-RNG, under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…The finding that the discriminability with STN stimulation was lowest on the block with the highest Go probability means that STN-DBS interfered with action restraint on trials when the Go response was most prepotent. Therefore, the results of our study and those of Hershey et al ( 2004 ) and Williams et al ( 2015 ) indicate that the effect of STN-DBS on performance of attention-demanding tasks requiring the ability to withhold prepotent responses is load-dependent. For example, Williams et al ( 2015 ) found that STN-DBS differentially impaired inhibition of habitual counting responses (count score 1) during paced RNG in a load-dependent fashion only at the fastest rate of 1 Hz, but not at the slower rates of 0.33 and 0.5 Hz.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The finding that the discriminability with STN stimulation was lowest on the block with the highest Go probability means that STN-DBS interfered with action restraint on trials when the Go response was most prepotent. Therefore, the results of our study and those of Hershey et al ( 2004 ) and Williams et al ( 2015 ) indicate that the effect of STN-DBS on performance of attention-demanding tasks requiring the ability to withhold prepotent responses is load-dependent. For example, Williams et al ( 2015 ) found that STN-DBS differentially impaired inhibition of habitual counting responses (count score 1) during paced RNG in a load-dependent fashion only at the fastest rate of 1 Hz, but not at the slower rates of 0.33 and 0.5 Hz.…”
Section: Discussionsupporting
confidence: 75%
“…STN-DBS does not affect global cognitive functioning in PD (Krack et al 2003 ; Follett et al 2010 ; Williams et al 2011 ; Rothlind et al 2014 ), and only isolated deficits in verbal fluency have been documented following surgery (Parsons et al 2006 ). However, there is evidence that executive control of action becomes worse with STN-DBS in PD (Frank et al 2007 ; Jahanshahi 2013 ; Jahanshahi et al 2015 ; Williams et al 2015 ). This was shown with various tasks of executive function, such as the Stroop (Jahanshahi et al 2000 ; Brittain et al 2012 ), fast-paced random number generation (Thobois et al 2007 ; Anzak et al 2011 ), the stop signal task (Ray et al 2012 ; Obeso et al 2014 ), the Go/NoGo task (Hershey et al 2004 , 2010 ; Kühn et al 2004 ; Ballanger et al 2009 ), the Simon interference task (Wylie et al 2010 ); and on tasks requiring decision-making under conflict (Frank et al 2007 ; Cavanagh et al 2011 ; Coulthard et al 2012 ; Zaghloul et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison of the results of the two studies raises interesting questions about the effect of STN-DBS in relation to task difficulty, which may have implications for theories of STN function. As previously noted (Jahanshahi 2013 ), to date, the STN-DBS-induced deficits in executive and inhibitory control have been mainly observed in conditions of high demand for cognitive control (Hershey et al 2004 ; Williams et al 2015 ) or motivational salience (Frank et al 2007 ). The interaction of STN-DBS with task difficulty is an issue of theoretical and clinical interest that is worth addressing in future studies.…”
Section: Discussionmentioning
confidence: 84%